Review on Intelligent Governance of Physical Fitness of College Students under the Background of Big Data - Qing Liu; Zhenzhi Li; Shangli Liu (Discrete Dynamics in Nature and Society)
The advent of the era of big data has promoted the reform of sports governance, and intelligent governance is becoming a strategic choice and a new trend to promote the physical fitness development of college students. Based on the profound analysis of the current situation of college students’ physical fitness, this study examines the great value of big data for the intelligent governance of physical fitness, and further constructs the model to achieve intelligent governance of college students’ physical fitness. The study also provides specific strategies to promote this process. According to the study, although the current situation of college students’ physical fitness is still not optimistic, data-driven intelligent governance of physical fitness provides a new solution to a personalized, refined, and diversified way of governance. By creating an intelligent governance concept with data thinking, building an intelligent governance platform supported by data, and by such measures as improving the data literacy of physical education teachers in colleges and universities and upgrading stadiums with intelligent techniques, the study seeks to break through the bottleneck of college students’ physical fitness governance and open up a new path to realize the effective governance of college students’ physical fitness.